Modeling crowd behavior based on the discrete-event multiagent approach - Лановой, Алексей Феликсович; Лановой, Артем Алексеевич (Eastern-European Journal of Enterprise Technologies, 2014)
The crowd is a temporary, relatively unorganized group of people, who are in close physical contact with each other. Individual behavior of human outside the crowd is determined by many factors, associated with his intellectual activities, but inside the crowd the man loses his identity and begins to obey more simple laws of behavior. One of approaches to the construction of multi-level model of the crowd using discrete-event multiagent approach was described in the paper. Based on this analysis the subject area, the problems, associated with the crowd model development were identified and described in the work. Approach to the construction of a model that takes into account such phenomena as a sharp change in direction of the velocity vector of the local flow of people in the crowd under the influence of physical, psychological and social factors, interagentinteraction, the change in thecrowddensity was described: - to form the simplified structure of the crowd model, it was proposed to use aggregative mathematical model that allows to divide all the objects, present in the crowd into the macro and micro-elements; - agent-oriented approach in the work was used to construct models of individual agents of the system, taking into account their dynamics and the presence of "driving" forcesin the crowd for a more accurate simulation of the crowd development; - using the detailing function of individual elements of the model in the work is designed to improve the adequacy of the model; it is made by the simultaneous introduction of macro-and micro-elements to the model with the ability to reassign their properties, jointlyform the conditions of boundary transitions through a single system of variables; - ensuring compatibility between the different elements of the same model is provided by introducing a unified system of constraints and shared variables, which allows to significantly simplify the software implementation of the model.